IMPROVING THE EXPORT PERFORMANCE OF INDONESIAN SMES THROUGH ENHANCED INTERNATIONAL MARKETING CAPABILITIES AMIDST THE CRISIS: UTILIZING FLEXIBLE STRATEGIES AND DIGITAL TECHNOLOGY - Zaenal Aripin; Fitriana; Farida Yulianty (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
This journal focuses on efforts to improve the export performance of Small and Medium Enterprises (SMEs) in Indonesia in the face of the global crisis situation. The research aims to investigate how improving international marketing capabilities, using flexible strategies, and utilizing digital technology can help SMEs overcome export challenges. The research methods used involved surveys, interviews, and data analysis. The results revealed that SMEs that successfully adopt these strategies tend to achieve better export growth than those that do not. They have the ability to adjust to changing global market demands and access a wider market through the utilization of digital technology. Therefore, it is important for SMEs to understand and implement these practices in their export activities. In addition, the journal also presents a discussion on the implications of the research results. Improved export performance of SMEs can have a positive impact on the national economy, create new jobs, and increase the competitiveness of domestic industries. Practical suggestions are also presented, such as international marketing training, access to digital technology, and cooperation with relevant government agencies and industries. This research provides valuable insights for Indonesian SMEs and relevant stakeholders to develop more effective strategies to improve export performance amidst the unpredictable global crisis.